The Effect Of Addiction To Playing Online Games On Learning Motivation In Students At Sdn Subangjaya 2, Sukabumi City - Ria Andriani; Burhanuddin Basri (Risenologi, 2022)
Nowadays online games are booming in the community, the fans are not half-hearted, from children to adults. The negative impacts of playing games include decreasing concentration in learning at home and at school. The goals of this study is the relationship between addiction to playing online games and learning motivation in students at SDN Subangjaya 2 Sukabumi City. The research design used was descriptive analytic with a cross sectional approach. Samples were taken by using Simple Random Sampling technique, namely 67 respondents. The instrument in this research is a questionnaire. The results of the study were analyzed using the Chi square formula. This study showed from the chi-square test results obtained P value: 0.000 <0.05, where it can be said that there is a relationship between addiction to playing online games with learning motivation in students at SDN Subangjaya 2 Sukabumi City. The conclusion in this study shows there is an effect of addiction to playing online games on learning motivation in students at SDN Subangjaya 2 Sukabumi City.